What Middle Schoolers Want to Talk About - Suzanna Smith (EDIS)
“Can your middle-schooler talk to you? Most 10- to 14-year-olds want a warm, close relationship with their parents. However, only about a quarter of adolescents nationwide find their parents ‘approachable and available to talk.’” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, March 2012.